Healthy Buddies™ Reduces Body Mass Index Z‐Score and Waist Circumference in Aboriginal Children Living in Remote Coastal Communities. (23rd July 2013) - Ronsley, Rebecca; Lee, Andrew S.; Kuzeljevic, Boris; Panagiotopoulos, Constadina
ABSTRACT: BACKGROUND: Aboriginal children are at increased risk for obesity and type 2 diabetes. Healthy Buddies™‐First Nations (HB) is a curriculum‐based, peer‐led program promoting healthy eating, physical activity, and self‐esteem. METHODS: Although originally designed as a pilot pre‐/post‐analysis of 3 remote Aboriginal schools that requested and received HB training, one school did not implement the program and was used as a control group. Outcomes included changes in body mass index z‐score (zBMI), waist circumference (WC), blood pressure (BP), self‐esteem, health behavior, and knowledge over 1 school year in kindergarten to grade 12 children. RESULTS: There was a significant decrease in zBMI (1.10 to 1.04, p = .028) and WC (77.1 to 75.0 cm, p < .0001) in the HB group (N = 118) compared with an increase in zBMI (1.14 to 1.23, p = .046) and a minimal WC change in the control group (N = 61). Prevalence of elevated BP did not change in the HB group, but increased from 16.7% to 31.7% in the control group (p = .026). General linear model analysis revealed a significant interaction between time, group, and zBMI (p = .001), weight status (p = .014), nutritious beverage knowledge (p = .018), and healthy living and self‐esteem score (p = .005). CONCLUSIONS: The HB program is a promising school‐based strategy for addressing obesity and self‐esteem in Aboriginal children.